PERTUMBUHAN DAN PRODUKSI BAWANG MERAH DENGAN PENGOLAHAN TANAH YANG BERBEDA DAN PEMBERIAN PUPUK NPK - Romayarni Saragih; B. Sengli J. Damanik; Balonggu Siagian (Universitas Sumatera Utara, 2014)
Research on title the growth and yield of shallot on different soil tillage and giving NPK fertilizerthis research was to determine growth and yield of Shallot on different soil tillage and Giving NPKfertilizer. This research had been conducted at Farm Resident on street Pasar I number 89, TanjungSari, Medan at ± 25 m asl from May until July 2013 using split plot design with two factor, i.e. SoilTillage (once tillage and twice tillage) and dose of NPK fertilizer (0; 0,6; 1,2; 1,8 and 2,4 g/ plant).Parameter observed were plant height, tillers number per sample, leaves number per sample, clovenumber per sample, wet weight tuber per sample, wet weight tuber per plot, dry weight tuber persample, dry weight tuber per plot and dry weight root per sample. The result showed different soiltillage treatment significantly affected on wet weight tuber per sample and dry weight tuber persample. NPK fertilizer treatment significantly effected on parameters plant height, wet weighttuber per sample, wet weight tuber per plot, dry weight tuber per sample and dry weight tuber perplot. The interaction of two factor not significantly affected all of parameter observed.Keywords : Soil Tillage, NPK Fertilizer, Shallot